Competency-based education: to the problem of implementation - Khazhismel G. Tkhagapsoev (Высшее образование в России, 2022)
The paper is devoted to a competency-based organization of university education in the country. It is shown that theoretical and methodological support of this innovative direction lags behind the needs of real practice, and this has already led to serious flaws in the federal state standards of the higher professional education of the third generation.